Conservation Strategy of Rafflesia zollingeriana Koord in Meru Betiri National Park, East Java - Lestari, Dewi; Hikmat, Agus; Zuhud, Ervizal Amir Muhammad (Jurnal Manajemen Hutan Tropika, 2014)
Rafflesia zollingeriana Koorders is a protected, rare, and endemic plants to Meru Betiri National Park.  However, its population was declined.  So, the study was focused on the analysis of the strengths, weaknesses, opportunities, and threats of conservation of R. zollingeriana to recommend some conservation's strategy and programs. This study was conducted at Meru Betiri National Park and its surrounding 5 villages. Data were collected by interviews, survey, observations, and literature studies. Qualitative data was analyzed by reduction, presentation and drawing conclusions simultaneously, while the quantitative data was analyzed descriptively. Matrix for SWOT analysis was processed by SPSS 16. The result showed that there were 4 elements that identified as strength, 5 elements that identified as weakness, 5 elements that identified as opportunity and 4 elements that identified as threat. The internal factor's value was higher than the external factor. The result of the SWOT analysis indicated that it needs aggresive strategy through collaboration among stakeholders to optimize both strength and opportunites. While the recommended program are: socialization the importance of R. zollingeriana conservation and developing a collaborative R. zollingeriana ecotourism.